Internationalisation in Vietnamese Higher Education (Higher Education Dynamics,, 2018)
This book focuses on models, strengths, opportunities, constraints and tensions in internationalisation in Vietnamese higher education. It reflects on key concepts from contemporary theories and models of internationalisation and discusses the implications for innovation, flexibility and responsiveness to local needs in Vietnam. Based on empirical research, theoretical knowledge and the experiences of researchers from Vietnam and overseas, the book draws out the distinctiveness and complexity of internationalisation practices and charts a way forward. It examines the key drivers and dimensions of internationalising Vietnamese higher education, and compares internationalisation in Vietnam to that in other countries. It clarifies and discusses tensions related to the appropriation of 'Western' internationalisation practice and models, and neo-liberal ideologies, to the local context of Vietnam. It provides readers with insights into government policy, quality assurance and benchmarking strategies, curriculum, the impact of international organisations on higher education, international student mobility, transnational education, employability, brain drain and brain gain and brain circulation.